2020
DOI: 10.1186/s12302-020-00328-3
|View full text |Cite
|
Sign up to set email alerts
|

Strategies adopted by Aphanizomenon flos-aquae in response to phosphorus deficiency and their role on growth

Abstract: Background: The N 2 -fixing cyanobacterium, Aphanizomenon flos-aquae is a globally distributed bloom causing species that degrades water quality of fresh and marine water bodies. Overcoming phosphorus (P) deficiency is one of the ecological advantages for bloom-forming cyanobacteria. It remains unclear to what extent can A. flos-aquae alleviate P deficiency by regulating P using strategies.Results: Based on in situ observations of extracellular alkaline phosphatase (APase) in A. flos-aquae via enzymelabeled fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…[26][27][28]. The Aphanizomenon genus might be adapted to environments with higher P concentrations having been sensitive to changes in ambient DP [29,30]. Aphanothece clathrata was also observed in some events at both sites (MB, 10 and 24 September 2018; PLSF 24 July and 5 August 2019) (Figure S2).…”
Section: Taxonomic Cyanobacterial Cell Counts and Compositionmentioning
confidence: 96%
See 2 more Smart Citations
“…[26][27][28]. The Aphanizomenon genus might be adapted to environments with higher P concentrations having been sensitive to changes in ambient DP [29,30]. Aphanothece clathrata was also observed in some events at both sites (MB, 10 and 24 September 2018; PLSF 24 July and 5 August 2019) (Figure S2).…”
Section: Taxonomic Cyanobacterial Cell Counts and Compositionmentioning
confidence: 96%
“…[26][27][28]. The Aphanizomenon genus might be adapted to environments with higher P concentrations having been sensitive to changes in ambient DP [29,30]. The bottom and top of the box shows the lower and upper quartiles, the band in between them shows the median, whiskers show the minimum and maximum (excluding outliers) and circles show the outliers.…”
Section: Taxonomic Cyanobacterial Cell Counts and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported, lakes rich in nitrogen can support the growth of diazotrophic species such as Aphanizomenon [29]. The growth of Aphanizomenon under phosphorus deficiency is probably related to their ability to use organic P from enzymatic process which takes from either intracellular or extracellular sources [30,31]. A study also reported that Merismopedia, which is non-nitrogen-fixing Cyanobacteria, dominates in water with high nitrogen concentration [32].…”
Section: Relative Abundance Of Major Speciesmentioning
confidence: 90%
“…Overall, it appears that C. ovalisporum competes strongly for DOP compared with other cyanobacterial species, hence may give it the capacity to dominate phytoplankton populations when DIP becomes limited. Chen et al [42] found that another cyanobacterium, Aphanizomenon flos-aquae could maintain growth from a one-off DOP supply for approximately 60 days via APA. The authors concluded that the coordination of dissolved DOP mineralization and continuous utilization of polyphosphate (a typical form of cellular P) might contribute to the maintenance of A. flos-aquae when relying on DOP.…”
Section: Discussionmentioning
confidence: 99%